E Government And Public Satisfaction Of Bandung City Government Accountability - et. al., Dini Arwati, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The government is the recipient of the mandate given by the public as the holder of the highest sovereignty. As a recipient of the mandate, the government must be accountable. The government must be accountable for its performance to the public. Along with the development of information technology, accountability information can be communicated through e government. With the existence of e government, the public can easily access the information they need and can obtain accountability information on government performance in a timely manner. However, the implementation of e-government in Indonesia still faces obstacles including the lack of integration of the performance accountability system with national planning and the weak capabilities of human resources, which will have an impact on public dissatisfaction as system users. This study aims to measure public satisfaction with government accountability based on government-based facilities. This study aims to determine the level of public satisfaction with the accountability of government performance through information contained in the government. The results show that the public is satisfied with the accountability of government performance